PENGARUH EKSTRAK KIMIA PADA UMPAN PANCING DASAR TERHADAP HASIL TANGKAPAN IKAN-IKAN KARANG DI SELAT BANGKA, MINAHASA UTARA - Reppie, Emil; Labaro, Ivor L. (Jurnal Teknologi Perikanan dan Kelautan, 2017)
Bottom hand lines have been used widely by coastal communities in North Sulawesi to catch coral fishes, since it simple in design, cheaper and easy to manage with a small boat. Although the gear’s design has evolved over centuries, there is still potential for improving its catching efficiency and selectivity. An attempt to understand the hooking process of bottom hand lining should therefore be focused on bait and how its chemical composition, visual and physical properties may stimulate target species to attack the bait and captured. Addition of chemical extracts to the bait could increase the fishing power of bottom hand line gear. But scientific information’s about its applications are not available yet. Therefore, the objective of this research was to study the effect of addition chemical extracts to bottom hand line baits toward the capture of coral fishes. Three kinds of chemical extracts were used to the slices of scad mackerel baits, they were power bait oil, squid liver oil, shrimp extract, and one bait without extract as a control. Catch data were collected using four unit of bottom hand lines, which operated in waters near coral reefs at the depth around 30 to 50 m; and analysis data were done based on randomized block design. The catch was 205 fish in total consist of 20 families and 29 species. Analysis of variance show that addition of chemical extracts to bottom hand line baits caused high significant effect in catch. Least significant differences test declared that the addition of three kinds of extract to the baits are not significant in catch; but power bait dan squid liver oil have high significant to the bait without extract; and no significant between shrimp extract and bait without extract